Combustion of Aluminum Particles near the Burning Surface in AP/AN Composite Propellants. Issue 5 (19th August 2015) - Doi, Rieko; Kuwahara, Takuo
Abstract Aluminum (Al) particles are commonly used in ammonium perchlorate (AP) composite propellants of solid rockets for increasing performance. When propellants including Al particles burn, Al particles easily agglomerate on the burning surface of the propellant. The diameters of agglomerated Al particles are greater than those of mixed particles. The combustion efficiency of the propellant decreases with increasing burning time of the agglomerated Al particles. Therefore, it is important to observe how the agglomerated Al particles burn on the burning surface of AP composite propellant. A lot of researchers have studied Al agglomerate characteristics. Previous studies clarified the relation between the agglomerated Al particle diameter and luminous flame diameter around Al particles near the burning surface. The shapes of luminous flames around agglomerated Al particles are spherical or elliptical. This study evaluates the shapes of the luminous flame around agglomerated Al particles at a constant diameter or a different diameter. When the proportion of the luminous flame diameter (Df) to the diameter of agglomerated Al particles (D0) is 1.54–1.71 at a constant D0, the luminous flames are almost perfectly spherical. Otherwise, the luminous flames are elliptical at a constant D0. Furthermore, when Df/D0 is close to the mean value, the luminous flame is more spherical than elliptical at different D0. The evaporation rate and the burning rate of Al vapor are inversely proportional to D0. The oxidation gas temperatures were changed and the activation energy of Al vapor was obtained as 39.2 kJ mol−1.